PEMBUATAN SISTEM INFORMASI MANAJEMEN KONSTRUKSI UNTUK MONITORING KEMAJUAN PEKERJAAN PROYEK JALAN - Nofi Yanti (Jurnal Teknologi Berkelanjutan, 2018)
Monitoring the physical and financial development of construction works currently are not integrated in an information system. In fact, there are many projects of road rehabilitation and maintenance at the country’s Construction Department in more than one location, resulting in PPK having difficulty in supervising and controlling the work of the contractors. The need for quick and easy access to information is very much needed by PPK in conducting monitoring and supervision so that obstacles in the field can be overcome immediately. Therefore it is necessary to create a road construction management information system to facilitate monitoring of work progress. The purpose of this research is to design an information system for PPK in directly monitoring work in order to facilitate and to assist PPK in carrying out their duties. The research method used is the waterfall model method by analyzing the problems faced by PPK by collecting data on user needs. From the data obtained in the form of job description information needs, physical and financial development progress in the form of reports and document management. From the data obtained, information system design is carried out with the stages of requirements, design, analysis, design, coding, system implementation, system validation and verification. The results of this study are the road monitoring construction management information system that can present physical and financial development progress data, contract data, service provider data, agency employee data and documentation reports. This information system can be viewed online so that all parties directly involved can enter data quickly and PPK can make the right decision.